Analisis Tugas Dan Kemampuan Seorang Guru Kelas Dalam Menyikapi Perbedaan Karakter Siswa Sekolah Dasar - Mila Lisnadiani Iswanda; Yayang Furi Furnamasari (Universitas Maritim AMNI Semarang, 2023)
This research was motivated by the rules that govern that to become a homeroom teacher, we cannot choose which level we want, because it is actually determined by the principal. For this reason, as prospective teachers, it is necessary to prepare themselves, one of which is by knowing how the attitudes and characteristics of children at each level of elementary school, in this case the differences in characteristics between low-grade students and high-grade students. This research uses the literature review method, by reviewing from various sources, such as journals and books. Hopefully this research can contribute to prospective class teachers to know what things must be prepared to become class teachers.